The impact of digital transformation on faculty performance in higher education: the mediating role of digital self-efficacy and the moderating role of task-technology fit - Sun, TingYu; Yoon, ManKeun (Frontiers in Psychology, 2025)
Faculty performance is a fundamental driver of sustainable development in higher education institutions. In the era of Education 4.0, the digitalization of education has had a profound impact on the faculty work content and methods. To investigate how digital transformation impacts faculty performance in higher education, this study surveyed 482 university faculty members. The results of the study showed that digital transformation is a significant positive predictor of faculty performance. Digital self-efficacy partially mediates the relationship between digital transformation and faculty performance. Task-technology fit positively enhances the impact of digital transformation on faculty performance. When the level of task-technology fit is high, the indirect effect of digital transformation on faculty performance through digital self-efficacy is stronger.